2005
DOI: 10.4049/jimmunol.175.11.7504
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Mechanism of Antibody-Mediated Clearance of Bordetella from the Lungs Requires TLR4

Abstract: Although the antibacterial effects of Abs are well studied in in vitro systems, the in vivo effects of Abs cannot always be accurately predicted. Complicated cross-talk between different effector functions of Abs and various arms of the immune system can affect their activities in vivo. Using the mouse respiratory pathogen Bordetella bronchiseptica, we examined the mechanisms of Ab-mediated clearance of bacteria from the respiratory tract. Interestingly, although TLR4 was not necessary for protective immunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 41 publications
5
48
2
4
Order By: Relevance
“…We have reported previously a defect in the immediate influx of neutrophils into the lungs of TLR4-defective mice following primary infection with B. pertussis (21). This is consistent with a report demonstrating that TLR4 is required for recruitment of neutrophils to the lungs, where they mediated Ab-mediated clearance of Bordetella bronchiseptica (40). IL-17 has already been shown to play a role in lung CXC chemokine production and neutrophil recruitment in host defense against K. pneumoniae infection (19,41).…”
Section: Discussionsupporting
confidence: 76%
“…We have reported previously a defect in the immediate influx of neutrophils into the lungs of TLR4-defective mice following primary infection with B. pertussis (21). This is consistent with a report demonstrating that TLR4 is required for recruitment of neutrophils to the lungs, where they mediated Ab-mediated clearance of Bordetella bronchiseptica (40). IL-17 has already been shown to play a role in lung CXC chemokine production and neutrophil recruitment in host defense against K. pneumoniae infection (19,41).…”
Section: Discussionsupporting
confidence: 76%
“…Antibodies may clear bacteria by neutralization, complement-mediated lysis, or opsonization for FcγR-mediated phagocytosis. We have previously shown that serum antibodies rapidly clear B. bronchiseptica from the lungs of mice and that the mechanism involved both complement and FcγRs (25,26). Since B. pertussis is very closely related to B. bronchiseptica but is cleared much more slowly by serum antibodies, we predicted that B. pertussis has some mechanism to resist 1 or more of these antibody effector functions early in the infection.…”
Section: Serum Antibodies Do Not Rapidly Clear B Pertussismentioning
confidence: 99%
“…We have previously shown that FcγR-bearing neutrophils are the primary inflammatory cells recruited to the lungs following infection with B. bronchiseptica and are required for rapid antibodymediated bacterial clearance (26,36). Since B. pertussis clearance required FcγRs, we sought to determine whether neutrophils are required for antibody-mediated clearance of this organism.…”
Section: Neutrophils Are Required For Antibody-mediated Clearance Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is an increasing incidence of B. pertussis infections in adolescents and adults, possibly due to waning immunity following the introduction of acellular vaccines into most developed countries (2). Adaptive immunity generated by previous infection or immunization with the whole-cell vaccine is effective at preventing severe disease, and studies in a mouse model suggested that a combination of Abs and Th1 and Th17 cells are involved (3)(4)(5)(6)(7). Protection against a primary infection with B. pertussis is mediated by innate and adaptive immune responses, and IFN-g secreted by NK and Th1 cells seems to be critical (4,8,9).…”
mentioning
confidence: 99%